New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China - Li, Qi-Li; Li, Li-Zhen; Gu, Fuang-Kang; Peng, Zhong (Zootaxa, 2016)
Material of the brachypterous Paederus of the Chinese provinces Henan, Anhui, Zhejiang, Hunan, Fujian, Guizhou, Sichuan, Shaanxi, Yunnan, Guangdong and Guangxi was examined. In total, twelve species are recognized, among which two are described here as new: P. daicongchaoi sp. n. (Anhui: Yaolouping) and P. nanlingensis sp. n. (Guangdong: Nanling). One species probably undescribed remains unnamed and one synonymy is proposed: Paederus (Gnathopaederus) bursavacua Willers, 2001 = Paederus (Gnathopaederus) daozhenensis Li & Zhou, 2009, nov. syn. A key to the brachypterous Paederus species of mainland China is provided.